A simple and effective evaluation method for lacustrine shale oil based on mass balance calculation of Rock-Eval data. (May 2022) - Li, Qiqi; Chen, Fengling; Wu, Shiqiang; Zhang, Liang; Wang, Yuxuan; Xu, Shang
Abstract: Because the profit from the development of unconventional resources can be small, success usually depends on the quick identification of favorable areas. It is therefore very important to identify a rapid and robust resource potential evaluation method. However, it is challenging to evaluate shale oil content, especially the recoverable oil part. We explore a new evaluation index (SE ) by using Rock-Eval data and mass balance. When SE ˃ 0, the shale interval has already expelled a certain amount of hydrocarbons, so it has poor shale oil potential. When SE is near 0, almost all the generated hydrocarbons are trapped in the shale itself, and simultaneously, no externally migrated hydrocarbons enter the shale. In the case of an SE near 0, the shale oil potential may depend on whether it is organic-rich; however, this type of shale tends to be compact and does not develop fractures. When SE ˂ 0, externally migrated hydrocarbons entered the shale interval, which usually indicates good shale oil potential. The more negative the SE is, the greater the shale oil potential. One of the advantages of this index is that it takes into account not only the residual oil content but also the conditions of hydrocarbon expulsion and migration. Moreover, this method is economical and convenient and is based on commonly available Rock-Eval data. Highlights: Three types of shale intervals can be divided according to the proposed new index. The method uses only routine Rock-Eval data to evaluate shale oil potential. The new index considers the conditions of hydrocarbon expulsion and migration. The combination of SE and OSI improves the shale oil potential prediction accuracy.